Critical theory and epistemology : the politics of modern thought and science - Marinopoulou, Anastasia (Manchester: Manchester University Press, 2019)
This volume in the 'Critical Theory and Contemporary Society' series explores the arguments between critical theory and epistemology in the twentieth and twenty-first centuries.
1 Phenomenology and hermeneutics 2 Structuralism and poststructuralism 3 Modernism and postmodernism 4 Systems theory 5 Critical realism Conclusions Index
Includes bibliographical references and index.
Keywords: Epistemology